Preparation method of lithium silicate in-situ modified silicon negative electrode material

By generating a lithium silicate protective layer on the surface of the silicon-based negative electrode material and performing carbon coating treatment, the problem of volume expansion of silicon material during lithiation is solved, and the cycle stability and safety of the battery are improved.

CN119601619AActive Publication Date: 2025-03-11CHINA THREE GORGES UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411681580.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-11
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The volume expansion of the silicon-based negative electrode material significantly during the lithiation process, resulting in electrode rupture, structural damage, increased interface impedance and electrical performance degradation, affecting the safety and performance of the battery.

Method used

Silicon powder is mixed with an oxidant, lithium source, carbon source and additives to form a protective layer of lithium silicate through hydrothermal reaction, and a carbon-coated lithium silicate in situ modified silicon composite material is prepared by low-temperature heat treatment process.

Benefits of technology

Effectively reduce the volume expansion of silicon material during the lithiation process, slow down the electrode deterioration rate, improve the circulation stability of the material, and reduce the safety risks of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601619A_ABST
    Figure CN119601619A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: mixing a silicon raw material with an oxidizing agent, a lithium source, a carbon source and an additive auxiliary material, then carrying out a hydrothermal reaction, and finally carrying out high-temperature carbonization to obtain the lithium silicate in-situ modified silicon-carbon composite negative electrode material. The composite material is composed of a lithium silicate in-situ modified silicon core and a carbon shell, and a carbon coating layer with the thickness of 20-30 nm is generated on the silicon surface. According to the method, the green and environment-friendly principle is followed in the raw material selection and preparation process, toxic waste is not generated, and the requirement of sustainable development is met. And the prepared finished product material has high purity, so that the battery performance can be improved, and the service life of the battery can be prolonged. The method is simple in preparation process, simple and convenient in required equipment operation, relatively low in manufacturing cost and suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon composite negative electrode material that can be used for lithium secondary batteries and a preparation method thereof, and belongs to the field of electrochemical power sources. Background Art

[0002] Against the backdrop of the rapid expansion of the global electric vehicle industry and energy storage industry, lithium-ion batteries (LIBs) are the core of electric vehicle power and energy storage systems, and their performance directly affects the safety, endurance and durability of vehicles. In order to alleviate the endurance anxiety of electric vehicles and improve the energy density of energy storage systems, one of the effective ways is to use high-specific capacity electrode materials. At present, the graphite anode materials used in most electric vehicle and energy storage system batteries have a low specific capacity (theoretical value is 372mAh / g), which limits the endurance of electric vehicles and the energy density and economic practicality of energy storage systems. Silicon-based anode materials are considered to be potential next-generation battery anode materials due to their excellent specific capacity (theoretical value is 3579 mAh / g) and moderate lithium insertion potential (0.2~0.4V). However, the volume expansion of silicon materials during the lithiation process is significant (more than 300%), which may lead to problems such as electrode rupture, structural damage, increased interface impedance and degradation of electrical performance, and also pose a threat to battery safety. Summary of the invention

[0003] In order to optimize the electrochemical performance of silicon materials and reduce side reactions, surface modification techniques such as carbon layer coverage and inorganic compound coating are widely used.

[0004] This study proposed an innovative artificial solid electrolyte modification structure for silicon surface, using silicon powder and industrially commonly used oxidants such as hydrogen peroxide (H2O2), potassium permanganate, and lithium sources such as lithium acetate (CH3COOLi·2H2O) and lithium carbonate as modifiers, and a mixture of carbon sources such as glucose and sucrose as raw materials for hydrothermal reaction. After the hydrothermal reaction, a lithium silicate protective layer was in situ generated on the surface of the silicon negative electrode material, and then a carbon-coated lithium silicate in situ modified silicon composite material was prepared by a low-temperature heat treatment process. This preparation method is simple, green and safe. The prepared composite material can effectively reduce the volume expansion of silicon materials during lithiation, slow down the electrode degradation rate, and improve the cycle stability of the material. At present, there are few studies on carbon-coated lithium silicate in situ modified silicon-based composite materials, and even fewer studies on silicon surface modification and carbon coating using a one-step method. Based on these analyses, it is of great significance to develop a preparation technology for carbon-coated lithium silicate in situ modified silicon composite negative electrode materials that is suitable for industrial-scale production and cost-effective.

[0005] The present invention aims to propose a lithium silicate in-situ modified silicon-carbon negative electrode material (Si@LSO@C) and a new preparation method thereof, which has simple operation, environmentally friendly manufacturing process, low manufacturing cost and good prospects for industrial mass production.

[0006] The specific technical solutions of the present invention are described below.

[0007] The present invention mixes silicon powder with an oxidant, a lithium source, a carbon source, and an additive auxiliary material, performs a hydrothermal reaction, and finally performs high-temperature carbonization to obtain a silicon-carbon composite negative electrode material modified in situ with lithium silicate.

[0008] This study proposed an innovative method to prepare silicon-carbon composite materials as battery negative electrode materials. The core of this method is to obtain silicon oxidation and lithium silicate in-situ modification in one step through hydrothermal reaction, and then combine with graphite material to form a composite material.

[0009] Specifically, the composite material consists of a silicon core and a carbon shell modified in situ by lithium silicate.

[0010] In the hydrothermal reaction stage, the patent of this invention describes in detail the formula parameters of various raw materials, the types of raw materials and the proportions of raw materials.

[0011] The silicon raw material includes micron silicon, nano silicon powder, or a mixture of micron silicon and nano silicon powder. The oxidant includes one or a combination of oxidants such as hydrogen peroxide (H2O2), potassium permanganate (KMnO4), potassium perchlorate (KClO4), etc. The lithium source includes one or more lithium sources such as lithium hydroxide (LiOH), lithium acetate (CH3COOLi), lithium carbonate (Li2CO2), etc. The carbon source includes one or more of glucose, sucrose, chitosan, asphalt, etc. The additive auxiliary materials include hexadecyltrimethylammonium bromide (CTAB), polyvinylpyrrolidone (PVP), oxalic acid (H2C2O2).

[0012] In addition, the invention patent describes in detail the hydrothermal reaction process parameters, including reaction temperature and reaction time. The temperature is between 101-300°C, preferably between 150-199°C. The reaction time is between 8-48 hours, preferably between 10-24 hours.

[0013] In addition, the present invention patent describes in detail the carbonization process parameters, including reaction temperature and reaction time. The temperature is between 350-1500°C, preferably between 550-950°C. The reaction time is between 3-48 hours, preferably between 5-12 hours.

[0014] The patent of this invention describes in detail the mass ratio of raw materials, silicon: oxidant: lithium source: carbon source: additive auxiliary material = (50~95): (0.1~20): (0.1-10): (0.1-50): (1~10).

[0015] Through these detailed steps and parameters, this study aims to provide an efficient and reproducible method to prepare lithium silicate in situ modified silicon-carbon composite anode materials to meet the needs of modern battery technology for high-performance anode materials.

[0016] Compared with the existing silicon-carbon composite anode material preparation technology, this study proposed a novel method, which is unique in the following aspects: (1) In the composite material prepared by this method, a hydrothermal synthesis method is used to obtain a lithium silicate coating on the surface of the silicon material in a one-pot process. Although the hydrothermal synthesis method is widely used in material synthesis, there are relatively few literature reports on the synthesis method of a lithium silicate coating on the surface of a single silicon without an oxide layer in situ by a one-pot method. The coating has the properties of a solid electrolyte, that is, it is insulating to electrons and permeable to ions.

[0017] (2) This method follows the principle of green environmental protection in the selection and preparation of raw materials, does not produce toxic waste, and meets the requirements of sustainable development. The prepared finished material has high purity, which helps to improve battery performance and extend its service life. The preparation process of this method is simple, the required equipment is easy to operate, the manufacturing cost is relatively low, and it is suitable for industrial large-scale production.

[0018] Through these innovations, this study aims to provide a new economical and environmentally friendly approach for the preparation of battery anode materials to meet the growing demand for energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 : X-ray diffraction pattern of Si@LSO@C composite material.

[0020] Figure 2 : High-resolution transmission electron microscopy (TEM) images of Si@LSO@C composite materials.

[0021] Figure 3 : Cycling performance curves of Si@LSO@C composite materials and pure silicon anode. DETAILED DESCRIPTION

[0022] This article will explain in detail the technical details of the present invention, including examples and control groups, to demonstrate the characteristics and advantages of the lithium silicate in-situ modified silicon-carbon composite material (Si@LSO@C) involved in the present invention. Please note that the examples mentioned do not cover all possible situations, and any other non-innovative embodiments proposed based on the embodiments of the present invention should also be regarded as the protection scope of the present invention. In order to more clearly demonstrate the advantages of the present invention, Examples 2-3 mainly adjust the raw materials for preparing Si@LSO@C in Example 1, Examples 4-5 mainly adjust the proportion of raw materials for preparing Si@LSO@C in Example 1, and Example 6 mainly adjusts some process parameters for preparing Si@LSO@C in Example 1. Example 7 mainly performs electrochemical performance test analysis on Si@LSO@C prepared in Examples 1-6. Control groups 1 to 4 do not contain oxidants, auxiliary materials, lithium sources, and carbon sources, respectively.

[0023] Example 1 5 grams of micron silicon (particle size D50 between 1-20 μm) was added to a hydrothermal reactor containing 100 g of water. After stirring with a magnetic stirrer for 30 minutes, 3 g of hydrogen peroxide solution (35 wt.%), 0.1 g of lithium carbonate, 0.3 g of carbon source glucose, and additives including 0.1 g of hexadecyltrimethylammonium bromide (CTAB), 0.1 g of polyvinylpyrrolidone (PVP), and 0.1 g of oxalic acid (H2C2O2) were added. At this time, silicon: oxidant: lithium source: carbon source: additive auxiliary material = 50:10.5:1:3:3. The hydrothermal reaction temperature was 180 ° C and the reaction time was 12 hours. After hydrothermal, it was filtered and dried in an oven at 60 ° C for 24 hours. The carbonization temperature was 650 ° C and the carbonization time was 6 hours.

[0024] The sample Si@LSO@C of this embodiment was subjected to X-ray diffraction (XRD) analysis, and diffraction peaks of silicon and lithium silicate can be detected. The XRD spectrum is shown in Figure 1 In addition, the transmission electron microscope (TEM) analysis of the sample Si@LSO@C in this embodiment shows that a carbon coating layer with a thickness of about 25 nm is generated on the silicon surface. The TEM image is shown in Figure 2 .

[0025] Example 2 Add 5 grams of nano-silicon (particle size D50 between 10-500nm) to a hydrothermal kettle containing 100g of water, stir with a magnetic stirrer for 30min, then add 1.05g of potassium permanganate, 0.1g of lithium carbonate, 0.3g of carbon source sucrose, and additives including 0.1g of hexadecyltrimethylammonium bromide (CTAB), 0.1g of polyvinylpyrrolidone (PVP), and 0.1g of oxalic acid (H2C2O2). At this time, silicon: oxidant: lithium source: carbon source: additives = 50:10.5:1:3:3. The hydrothermal reaction temperature is 180℃, and the reaction time is 12 hours. After hydrothermal, it is filtered and dried in an oven at 60℃ for 24 hours. The carbonization temperature is 650℃, and the carbonization time is 6 hours.

[0026] Example 3 Add 5 grams of micron silicon (particle size D50 between 1-20μm) to a hydrothermal reactor containing 100g of water, stir with a magnetic stirrer for 30min, then add 3g of oxidant hydrogen peroxide solution (35 wt.%), 0.1g of lithium carbonate, 0.3g of carbon source glucose, and 0.3g of hexadecyltrimethylammonium bromide (CTAB). At this time, silicon: oxidant: lithium source: carbon source: additive auxiliary material = 50:10.5:1:3:3. The hydrothermal reaction temperature is 180℃, and the reaction time is 12 hours. After hydrothermal, it is filtered and dried in an oven at 60℃ for 24 hours. The carbonization temperature is 650℃, and the carbonization time is 6 hours.

[0027] Example 4 5 grams of micron silicon (particle size D50 between 1-20 μm) was added to a hydrothermal reactor containing 100 g of water. After stirring with a magnetic stirrer for 30 minutes, 1 g of hydrogen peroxide solution (35 wt.%), 0.05 g of lithium carbonate, 0.1 g of carbon source glucose, and additives including 0.1 g of hexadecyltrimethylammonium bromide (CTAB), 0.1 g of polyvinylpyrrolidone (PVP), and 0.1 g of oxalic acid (H2C2O2) were added. At this time, silicon: oxidant: lithium source: carbon source: additives = 50:3.5:0.5:1:3. The hydrothermal reaction temperature was 180 ° C and the reaction time was 12 hours. After hydrothermal, it was filtered and dried in an oven at 60 ° C for 24 hours. The carbonization temperature was 650 ° C and the carbonization time was 6 hours.

[0028] Example 5 Add 5 grams of micron silicon (particle size D50 between 1-20 μm) to a hydrothermal reactor containing 100 g of water, stir with a magnetic stirrer for 30 minutes, then add 1 g of oxidant hydrogen peroxide solution (35 wt.%), 0.05 g of lithium carbonate, 0.1 g of carbon source glucose, and additives including 0.1 g of hexadecyltrimethylammonium bromide (CTAB) and 0.1 g of polyvinylpyrrolidone (PVP). At this time, silicon: oxidant: lithium source: carbon source: additives = 50:3.5:0.5:1:2. The hydrothermal reaction temperature is 180 ° C and the reaction time is 12 hours. After hydrothermal, it is filtered and dried in an oven at 60 ° C for 24 hours. The carbonization temperature is 650 ° C and the carbonization time is 6 hours.

[0029] Example 6 5 grams of micron silicon (particle size D50 between 1-20 μm) was added to a hydrothermal reactor containing 100 g of water. After magnetic stirring for 30 minutes, 3 g of hydrogen peroxide solution (35 wt.%), 0.1 g of lithium carbonate, and 0.3 g of carbon source glucose were added. The additives and auxiliary materials included 0.1 g of hexadecyltrimethylammonium bromide (CTAB), 0.1 g of polyvinylpyrrolidone (PVP), and 0.1 g of oxalic acid (H2C2O2). At this time, silicon: oxidant: lithium source: carbon source: additive auxiliary material = 50:10.5:1:3:3. The hydrothermal reaction temperature was 200 ° C and the reaction time was 16 hours. After hydrothermal, it was filtered and dried in an oven at 60 ° C for 24 hours. The carbonization temperature was 850 ° C and the carbonization time was 12 hours.

[0030] Example 7 The samples of Examples 1-6 were subjected to button cell tests to evaluate their capacity and charge-discharge cycle characteristics. The button cell preparation steps for all samples in the present invention are as follows: the active material, acetylene black (CB) and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 70:20:10 and dissolved in N-methylpyrrolidone (NMP) to form a slurry. Subsequently, the slurry is evenly coated on the surface of the copper foil and dried in a vacuum environment for 12 hours. Metal lithium foil is used as the negative electrode, and a polypropylene separator (PP, 20 microns) and an electrolyte (the solvent ratio is DMC:EMC:EC=5:3:2, the LiPF6 concentration is 1.1M, and FEC accounts for 1.5% of the total volume of the electrolyte) are assembled into a 2025-type button cell. When performing charge and discharge tests, the current density is set to 1 A / g, and the voltage window is set between 0.01 and 1.5V. The test results are shown in Figure 3 Compared with other embodiments, the material cycle stability of embodiment 1 is significantly improved.

[0031] Comparative Example 1 The reaction raw materials are similar to those in Example 1, but no oxidant is added. Specifically, 5 grams of micron silicon (particle size D50 between 1-20 μm) is added to a hydrothermal kettle containing 100g of water, stirred with a magnetic stirrer for 30 minutes, 0.1g of lithium source Li2CO3 (battery grade), and 0.3g of carbon source glucose are added. The additive auxiliary materials include 0.1g of hexadecyltrimethylammonium bromide (CTAB), 0.1g of polyvinylpyrrolidone (PVP), and 0.1g of oxalic acid (H2C2O2). At this time, silicon: oxidant: lithium source: carbon source: additive auxiliary material = 50:10.5:1:3:3. The hydrothermal reaction temperature is 180°C and the reaction time is 12 hours. After hydrothermal, it is filtered and dried in an oven at 60°C for 24 hours. The carbonization temperature is 850°C and the carbonization time is 12 hours.

[0032] Comparative Example 2 The reaction raw materials are similar to those in Example 1, but no auxiliary materials are added. Specifically, 5 grams of micron silicon (particle size D50 is between 1-20 μm) is added to a hydrothermal kettle containing 100g of water, and then 3g of the oxidant hydrogen peroxide solution (35 wt.%) is added. After stirring with a magnetic stirrer for 30 minutes, 0.1g of lithium carbonate and 0.3g of carbon source glucose are added. At this time, silicon: oxidant: lithium source: carbon source: additive auxiliary material = 50:10.5:1:3:3. The hydrothermal reaction temperature is 180°C and the reaction time is 12 hours. After hydrothermal, it is filtered and dried in an oven at 60°C for 24 hours. The carbonization temperature is 850°C and the carbonization time is 12 hours.

[0033] Comparative Example 3 The reaction raw materials are similar to those in Example 1, but no lithium source is added. Specifically, 5 grams of micron silicon (particle size D50 between 1-20 μm) is added to a hydrothermal kettle containing 100 g of water, and then 3 g of oxidant hydrogen peroxide solution (35 wt.%) is added. After stirring with a magnetic stirrer for 30 minutes, 0.3 g of carbon source glucose is added, and the additive auxiliary materials include 0.1 g of hexadecyltrimethylammonium bromide (CTAB), 0.1 g of polyvinylpyrrolidone (PVP), and 0.1 g of oxalic acid (H2C2O2). At this time, silicon: oxidant: lithium source: carbon source: additive auxiliary material = 50:10.5:1:3:3. The hydrothermal reaction temperature is 180°C and the reaction time is 12 hours. After hydrothermal, it is filtered and dried in an oven at 60°C for 24 hours. The carbonization temperature is 850°C and the carbonization time is 12 hours.

[0034] Comparative Example 4 The reaction raw materials are similar to those in Example 1, but no carbon source is added. Specifically, 5 grams of micron silicon (particle size D50 between 1-20 μm) is added to a hydrothermal kettle containing 100 g of water, and then 3 g of oxidant hydrogen peroxide solution (35 wt.%) is added, and after stirring with a magnetic stirrer for 30 minutes, 0.1 g of lithium carbonate, and additives and auxiliary materials include 0.1 g of hexadecyltrimethylammonium bromide (CTAB), 0.1 g of polyvinylpyrrolidone (PVP), and 0.1 g of oxalic acid (H2C2O2). At this time, silicon: oxidant: lithium source: carbon source: additive auxiliary material = 50:10.5:1:3:3. The hydrothermal reaction temperature is 180 ° C, and the reaction time is 12 hours. After hydrothermal, it is filtered and dried in an oven at 60 ° C for 24 hours. The carbonization temperature is 850 ° C, and the carbonization time is 12 hours.

Claims

1. A lithium silicate in-situ modified silicon negative electrode material, characterized in that: The composite material consists of a silicon core and a carbon shell in situ modified by lithium silicate, and a carbon coating layer with a thickness of 20-30 nm is generated on the silicon surface; the composite material contains characteristic peaks at about 24°, about 24.5°, about 25°, about 28°, and about 44°.

2. A method for preparing a lithium silicate in-situ modified silicon negative electrode material according to claim 1, characterized in that: The silicon raw material is mixed with an oxidant, a lithium source, a carbon source, and additive auxiliary materials, and then subjected to a hydrothermal reaction. Finally, after high-temperature carbonization, a silicon-carbon composite negative electrode material modified in situ with lithium silicate is obtained.

3. The method for preparing a silicon negative electrode material modified by lithium silicate in situ according to claim 2, characterized in that: The mass ratio of silicon: oxidant: lithium source: carbon source: additive auxiliary material is (50~95):(0.1~20):(0.1-10):(0.1-50):(1~10).

4. The method for preparing a lithium silicate in-situ modified silicon negative electrode material according to claim 2, characterized in that: The silicon raw material includes micron silicon, nano silicon powder, or a mixture of micron silicon and nano silicon powder.

5. The method for preparing a lithium silicate in-situ modified silicon negative electrode material according to claim 2, characterized in that: The oxidant includes one or a combination of hydrogen peroxide, potassium permanganate, and potassium perchlorate.

6. The method for preparing a lithium silicate in-situ modified silicon negative electrode material according to claim 2, characterized in that: The lithium source includes one or more of lithium hydroxide, lithium acetate and lithium carbonate; The carbon source includes one or more of glucose, sucrose, chitosan and asphalt; The additive auxiliary materials include one or more of cetyltrimethylammonium bromide, polyvinylpyrrolidone and oxalic acid.

7. The method for preparing a silicon negative electrode material modified by lithium silicate in situ according to claim 2, characterized in that: The hydrothermal reaction temperature is between 101-300° C., preferably between 150-199° C.; the reaction time is between 8-48 hours, preferably between 10-24 hours.

8. The method for preparing a lithium silicate in-situ modified silicon negative electrode material according to claim 2, characterized in that: The high-temperature carbonization temperature is between 350-1500° C., preferably between 550-950° C.; the reaction time is between 3-48 hours, preferably between 5-12 hours.

9. A lithium ion battery, characterized in that: The invention comprises the lithium silicate in-situ modified silicon negative electrode material as described in claim 1 or the lithium silicate in-situ modified silicon negative electrode material prepared by the method as described in any one of claims 2-8.

10. A button battery, characterized in that: The invention comprises the lithium silicate in-situ modified silicon negative electrode material as described in claim 1 or the lithium silicate in-situ modified silicon negative electrode material prepared by the method as described in any one of claims 2-8.

Citation Information

Patent Citations

  • Lithium ion battery composite negative electrode material and preparation method thereof

    CN107887587A

  • Carbon-coated silicon-based negative electrode material and preparation method thereof

    CN112164779A

  • Silicon-carbon negative electrode material, preparation method and application thereof

    CN116364935A

  • Lithium silicate-silicon coated LiF-C composite material with gradient lithium distribution and preparation and application thereof

    CN117594759A

  • In-situ carbon-coated lithium-supplementing silicon-carbon negative electrode material, preparation method and application

    CN118315552A